Students’ Perception as Review Providers and Receivers on Writing - Santi Indriani, Ketut; Widiastuti, Ni Made Ayu (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
Many studies found out that peer review can improve students' abilities in writing activities. In conducting peer reviews, students carry out two roles, namely as review providers and receivers. Do these two roles have a positive impact on improving writing skills? To answer this question, this study aims to identify students' perceptions as review providers and receivers on writing activities and to analyze the comparison of the benefits received from the role of review providers and receivers. The data in this study were taken from 50 second semester students who took the intermediate writing course at the English Department, Faculty of Humanities, Udayana University. The instrument used in the data collection was a questionnaire consisting of 40 closed questions. The obtained data was analyzed descriptive qualitatively. The results of data analysis show that review receivers get greater benefits from peer review activities compared to providers. The benefits of peer review are far greater for receivers, especially in terms of better thesis statement formulation and better grammar used in their essay writing. The benefits of peer review for review providers and receivers in terms of increasing vocabulary are almost the same. However, overall it can be stated that the review provider and receiver gave a positive response to the peer review method in essay writing.